Should Sickle Cell Trait Be a Contraindication to Breast Reconstruction?—A Case Series Analysis - Webster, Theresa K.; Araya, Sthefano; Bartolacci, Joseph; Amadio, Grace M.; Panichella, Juliet C.; Costa, Joseph; Patel, Sameer A. (Journal of Reconstructive Microsurgery Open, 2023)
Background While sickle cell disease has long been considered a contraindication to breast free flap reconstruction, there have been less definitive decisions about the impact of sickle cell trait on these procedures. We sought to analyze the patients with sickle cell trait who underwent free deep inferior epigastric perforator (DIEP) flap and pedicled latissimus dorsi (LD) flap at a single institution to determine the reconstructive outcomes.Methods Patients with sickle cell trait who underwent breast free DIEP and pedicled LD reconstruction from 2007 to 2021 at a single institution by the lead surgeon were analyzed for demographics and surgical outcomes.Results Four patients were identified as having sickle cell trait and having undergone a breast flap reconstruction. The average age of the patients was 54 years, median body mass index was 25, and past medical history was notable for one patient being a current smoker, and one patient having hypertension. Two patients received a unilateral free DIEP flap, one received a bilateral free DIEP flap, and one received a unilateral pedicled LD flap for a total of five flaps in four patients. Three of the patients received prior hormone therapy, one received prior radiation therapy, and one received prior chemotherapy. There were no instances of flap failure, vessel thrombosis, pulmonary embolism, or deep venous thrombosis. One patient experienced wound dehiscence.Conclusion In this case series we present four patients with sickle cell trait who successfully underwent breast flap reconstruction without any instances of flap or systemic thrombosis. More work is needed to determine how to pre- and postoperatively optimize patients with sickle cell trait for favorable breast flap reconstruction outcomes.
Keywords: deep inferior epigastric perforator free flap; latissimus dorsi flap; DIEP; sickle cell trait; breast reconstruction; autologous breast reconstruction